2022
DOI: 10.1021/acsomega.2c00225
|View full text |Cite
|
Sign up to set email alerts
|

DNA-Binding Properties of Bis-N-substituted Tetrandrine Derivatives

Abstract: A series of bis- N -substituted tetrandrine derivatives carrying different aromatic substituents attached to both nitrogen atoms of the natural alkaloid were studied with double-stranded model DNAs (dsDNAs) to examine the binding properties and mechanism. Variable-temperature molecular recognition studies using UV–vis and fluorescence techniques revealed the thermodynamic parameters, Δ H , Δ S , and Δ G , showing that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…In this sense, there are some works about tetrandrine derivatives with antiproliferative activity against various tumor cell lines. However, to the best of our knowledge, there are no reports documenting other biological properties of tetrandrine derivatives. Our research group is a pioneer in the chemical modification of the tetrandrine alkaloid, based on the alkylation of its nitrogen atoms, as well as in the physicochemical and molecular recognition studies of this type of derivatives toward anions of biological importance, such as DNA. More recently, we have also studied the antiproliferative activity in various cancer cell lines for some of these derivatives. , In this context, the mono- N -substituted derivatives with acridine and anthracene MAcT and ManT , respectively (Figure ), , were shown to have good antiproliferative activity, with an outstanding IC 50 of 2.74 μg/mL for ManT against HeLa cervical cancer cell line, a value 3.3 times lower than that of natural tetrandrine. Furthermore, it was also shown that both derivatives have good affinity toward ds-DNA under physiological conditions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this sense, there are some works about tetrandrine derivatives with antiproliferative activity against various tumor cell lines. However, to the best of our knowledge, there are no reports documenting other biological properties of tetrandrine derivatives. Our research group is a pioneer in the chemical modification of the tetrandrine alkaloid, based on the alkylation of its nitrogen atoms, as well as in the physicochemical and molecular recognition studies of this type of derivatives toward anions of biological importance, such as DNA. More recently, we have also studied the antiproliferative activity in various cancer cell lines for some of these derivatives. , In this context, the mono- N -substituted derivatives with acridine and anthracene MAcT and ManT , respectively (Figure ), , were shown to have good antiproliferative activity, with an outstanding IC 50 of 2.74 μg/mL for ManT against HeLa cervical cancer cell line, a value 3.3 times lower than that of natural tetrandrine. Furthermore, it was also shown that both derivatives have good affinity toward ds-DNA under physiological conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Our research group is a pioneer in the chemical modification of the tetrandrine alkaloid, based on the alkylation of its nitrogen atoms, as well as in the physicochemical and molecular recognition studies of this type of derivatives toward anions of biological importance, such as DNA. 27 35 More recently, we have also studied the antiproliferative activity in various cancer cell lines for some of these derivatives. 32 , 35 In this context, the mono- N -substituted derivatives with acridine and anthracene MAcT and ManT , respectively ( Figure 1 ), 32 , 33 were shown to have good antiproliferative activity, with an outstanding IC 50 of 2.74 μg/mL for ManT against HeLa cervical cancer cell line, a value 3.3 times lower than that of natural tetrandrine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation